Analisis Gaya Pengasuhan Orangtua terhadap Keterlambatan Berbicara Anak Usia Empat Tahun - Hotmauli Damanik, Meirani; Aini, Azizah; Ananda, Nur Arani; Siregar, Masyunita; Hasni, Uswatul; Surya Amanda, Rizki (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Speech development delays in children are often triggered by inappropriate parenting styles during their developmental stages. This research employs a qualitative descriptive method to analyze parenting styles, particularly permissive parenting, concerning speech delays in 4-year-old children. Factors such as parental busyness, low educational levels, lack of stimulation, positive support from the environment, and limited interaction are identified as major contributors to the issue. Research findings highlight that permissive parenting influences the language development of children through a lack of positive examples, adequate stimuli, and guidance from parents.